Pengembangan Standar Operasional Prosedur (SOP) untuk Mengembangkan Karakter Anak Usia Dini di TK Islam Kota Mataram Tahun 2021 - Nurul Haniza; Nurhasanah Nurhasanah; Ika Rachmayani; I Nyoman Suarta (Indonesian Publication Center, 2021)
This research is motivated by the teacher's lack of knowledge in compiling and implementing SOPs to develop the character of early childhood. The preparation and application of SOPs to develop the character of early childhood that is less than optimal can cause the development of children's character to be hampered. The purpose of this study was to find out how the steps for preparing and implementing SOPs were to develop the character of early childhood in Islamic Kindergarten in Mataram City. This type of research is a qualtative. While the research method used is the development method. The research subjects were teachers and school principals. The data collection techniques used were observation, interviews, FGDs, and documentation. Data analysis was carried out descriptively and qualitatively sorted according to the evaluation components of context, input, process and product. The result of this research is the formation of a product in the form of SOP to develop the character of early childhood. From this study it can be concluded that the formation of early childhood character can be done by applying SOPs to develop early childhood character. The steps for preparing SOPs to develop the character of early childhood are as follows: The first step is to determine the type of SOP to be compiled. The second step is to determine the character that you want to form in the PAUD unit. The third step is to determine the activities to be carried out based on the competencies that have been determined. The fourth step, Determine the goals for each activity that has been selected. The fifth step is to draw up the steps that will be taken for character development. The sixth step is to draw up SOPs to develop the character of early childhood.